Autopoiesis And Organizational Communication: How The Jember Fashion Carnaval Adapts Through Communicative Processes - As'adi, Mohamad Hasan; Haryadi, Fransiskus Trisakti; Raya, Alia Bihrajihant; Wahyuni, Hermin Indah (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2025)
This study examines the adaptation of the Jember Fashion Carnaval (JFC) organization to the dynamic social connectivity of its environment. Utilizing a qualitative approach and digital ethnography, the research analyzes the organization's responses, interpenetration, and adaptation strategies. Findings indicate that JFC demonstrates responsiveness through innovative carnival themes and diverse communication channels. However, limitations arise from programmatic constraints and individual influences within the organization. Furthermore, JFC's interpenetration into various societal sectors, including education, economy, and culture, shapes its policies and decisions. This adaptation manifests in the evolution of fashion design, event concepts, and community-inclusive management. This research contributes to understanding organizational adaptation within a rapidly changing socio-cultural context, highlighting the interplay between organizational systems and their environment. Employing Niklas Luhmann's social systems theory, specifically the concept of autopoiesis, this study offers a unique perspective on how JFC, as an organizational system, maintains its identity while adapting to its surroundings. The results provide valuable insights for the field of development communication and challenge traditional approaches that focus on internal organizational factors by emphasizing the importance of external factors in shaping organizational behavior.